PENGARUH STRUKTUR DAN BUDAYA ORGANISASI TERHADAP INOVASI ORGANISASI PERUSAHAAN - Fransiska Ekobalawati (Derivatif : Jurnal Manajemen, 2020)
The research aims to study the influence of organizational structure and culture on corporate organizational innovation. The method used is a quantitative method by collecting 100 questionnaire samples. This study analyzes the data collected with multiple regression analysis. The independent variable of this research is the organizational structure and culture of the organization while the dependent variable of this research is innovation within the company. The result of this research is that the organizational structure and culture of the organization has a significant and positive influence on a company’s innovation.Keywords: Innovation, Organizational Structure, Organizational Culture